2008
DOI: 10.1016/j.jcrs.2007.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Subtle signs of anterior vitreous face disturbance during posterior capsulorhexis in pediatric cataract surgery

Abstract: In 4 patients with congenital cataract, subtle signs of anterior vitreous face (AVF) disturbance were documented during posterior continuous curvilinear capsulorhexis. The signs were vitreous strands in the anterior chamber, vitreous strands attached to the capsule flap, and distortion of the anterior and posterior capsulorhexis margins; the latter is considered a pathognomonic sign of AVF disturbance. As a result of the early recognition, modifications to the cataract surgery technique were made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…We have modified the technique by injecting an ophthalmic viscosurgical device (OVD) around the area of the initial puncture to achieve a flat or concave capsule. 46,47 Manual posterior capsulorhexis remains the gold standard because it yields a smooth, round edge and also offers resistance to capsule tearing. [48][49][50] However, several authors have observed that performing PCCC is technically difficult.…”
Section: Manual Posterior Continuous Curvilinear Capsulorhexismentioning
confidence: 99%
See 1 more Smart Citation
“…We have modified the technique by injecting an ophthalmic viscosurgical device (OVD) around the area of the initial puncture to achieve a flat or concave capsule. 46,47 Manual posterior capsulorhexis remains the gold standard because it yields a smooth, round edge and also offers resistance to capsule tearing. [48][49][50] However, several authors have observed that performing PCCC is technically difficult.…”
Section: Manual Posterior Continuous Curvilinear Capsulorhexismentioning
confidence: 99%
“…However, anterior vitreous face disturbance is a potential complication associated with this procedure. 46,47 It can occur during the puncture to initiate the PCCC, during the maneuver to elevate a flap, or while attempting to regrasp the capsule with the forceps. 46,47 In a study by Dholakia et al, 46 a primary PCCC was completed in the 106 eyes and anterior vitreous face disturbance was reported in only 5 eyes (4.7%) of children younger than 2 years of age.…”
Section: Manual Posterior Continuous Curvilinear Capsulorhexismentioning
confidence: 99%
“…This maneuver, along with frequent regrasping, enables the surgeon to make a PCCC of the desired size without anterior vitreous face disruption. 7 The diagnostic signs of an intact anterior vitreous face are a smooth contiguous contour and a homogenous staining pattern of 3 buttonholes, giving the impression of a tabletop configuration with 3 subramifications. No portion of the vitreous should extend into the anterior segment, suggesting that the 3 buttonholes are probably the physiological depressions in the anterior vitreous face.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although there are numerous descriptions of the clinical morphology of the anterior vitreous face using a slitlamp biomicroscope, 8,9 there is little information on the intraoperative morphology of the anterior vitreous pertinent to cataract surgery. We describe the intraoperative morphology of the intact anterior vitreous face with the aid of triamcinolone acetonide.…”
mentioning
confidence: 99%
“…28 High-viscosity viscoelastic sodium hyaluronate is injected around the area of the initial puncture to achieve a flat or concave capsule. 29,30 The ends of the tear are grasped with microforceps (ASICO, Westmont, IL, USA) and moved circumferentially to create a circular opening in the posterior capsule. The end result should be a PCCC concentric to and smaller than the anterior capsulorhexis.…”
Section: Eyementioning
confidence: 99%